ANALISIS PENGUJIAN STATIS MOTOR MATIC 110 CC MENJADI MOTOR LISTRIK 2 KW - Sinambela, Rismen (Jurnal Rekayasa Mesin, 2025)
Electric motorbike conversion is one of the right solutions to reduce carbon emissions, alternative energy to replace depleting fossil fuels, reduce the impact of congestion and the expensive price of electric motorbikes. For this reason, information is needed in terms of proper planning, design, and calculation of operational activities related to efficiency, cost, safety, energy saving, quality, and maintenance. The planning of an electric motorbike using a 2 kW 72 Volt 20 Ah BLCD motor, a 72 V 500Watt controller, and a 72 V 20 Ah Gesits li-NCM battery, conducted static testing for one hour against speed variations of 30, 50, and 70 km/hour. This study shows that, the electric motorbike at the highest speed of 70 km / h the battery temperature is stable at 37.9 ° C below 45 ° C in the package, power 1,472.91 Watt, current 20.58 A, voltage 71.57 Volts, torque 4.5 Nm, battery consumption 39.8%, charging time 1.59 hours and costs incurred of Rp 645.82. It is clear that electric motorbikes have better value in terms of features, energy usage, running costs, and battery temperature than combustion motors.